Determinants of Stunting in Landak District - Palge, Gebiyola; Suwarni, Linda; Selviana, Selviana (Ahmar Metastasis Health Journal, 2024)
Stunting becomes one of the obstacles in Indonesia's achievement of the gold of 2045. The number of stunting incidents in the West Kalimantan Province is still high at 24.5% in 2023. Landak district also includes the highest number, which is 31.0%. The study aims to analyze the determinants of stunting incidence in the Landak District. The type of research used is analytical research with a cross-sectional approach. The total sample of 148 respondents was obtained through total sampling. Data analysis was carried out univariately and bivariate with Chi-Square statistical tests. In this study, maternal age during pregnancy, the history of Low Birth Weight, non-exclusive breastfeeding, and early Breastfeeding Complementary Food (MP-ASI) are determinants of stunting (p-value < 0.05). It is necessary to educate adolescents about the maturity of the marriage age and future mothers about patterns of childcare.